Identification of a Large Novel Imprinted Gene Cluster on Mouse Proximal Chromosome 6 - Ono, Ryuichi (Cold Spring Harbor Laboratory Press, 2003)
Mice with maternal duplication of proximal chromosome 6 die in utero at an early embryonic stage. Recently, two imprinted genes, paternally expressed Sgce and maternally expressed Asb4, were identified in this region. This report analyzes the imprinting status of genes within a 1-Mb region containing these two genes. Peg10, which is next to Sgce, shows complete paternal expression, like Sgce. Conversely, Neurabin, Pon2, and Pon3 show preferential maternal expression at embryonic stages, although they all show biallelic expression in neonatal tissues. These results demonstrate that there is a large novel imprinted gene cluster in this region. 5′-RACE (Rapid Amplification of cDNA Ends) analysis of Peg10 revealed the existence of a novel first exon separate from the second exon, which encoded two putative ORFs similar to the viral Gag and Pol proteins. A differentially methylated region established in sperm and eggs is located just within the region containing the two first exons of Peg10 and Sgce, and may play an important role in regulating the two paternally expressed genes: Peg10 and Sgce.